Exploring potential causal relationships between gut microbiota, inflammatory factors, and postpartum depression: a Mendelian randomization analysis - Hui Li; Hongyan Meng; Chunxiao Dang; Pengfei Liu; Jinxing Liu; Xiao Yu; Zhonglin Wang; Lilv; Xiaohui Sui (BMC Pregnancy and Childbirth)
Abstract Background Recent studies have suggested a potential correlation between ecological dysregulation of the gut microbiota (GM) and the onset and development of postpartum depression (PPD). In addition, inflammatory factors (IFs) have been reported to play an important role in the development of PPD. However, the causal connections among GM, IFs, and PPD remain to be understood. Objective This study sought to determine if genetically predicted GM and IFs exert a causal effect on PPD and to study whether IFs mediate the causal effect of GM on PPD. Methods Two-step and two-sample Mendelian randomization (MR) analyses, primarily employing the inverse variance weighted (IVW) method, were conducted to evaluate the causal relationship between GM, IFs, and PPD, and to assess potential mediating effects. Heterogeneity and horizontal pleiotropy tests were performed to evaluate the robustness of the findings and the strength of the causal associations. Results Class Alphaproteobacteria, genus Family XIII AD3011 group exhibited a positive association with PPD risk; whereas, the family Clostridiales vadin BB60 group, family Veillonellaceae, genus Ruminococcaceae UCG011, and the inflammatory factors C–C motif chemokine ligand 5 (CCL5) and C–C motif chemokine ligand 3 (CCL3) demonstrated negative correlations with PPD risk. IFs did not exhibit a mediating role. No heterogeneity or horizontal pleiotropy was observed. Conclusions Our MR study offered genetic evidence that GM and IFs contribute to the pathogenesis of PPD, with no mediating effect of IFs. This enhances our understanding of PPD's pathological mechanisms and offers new perspectives for developing novel preventative and therapeutic strategies.